One Health: past successes and future challenges in three African contexts. - Anna L Okello; Kevin Bardosh; James Smith; Susan C Welburn (Public Library of Science (PLoS), 2014)
The recent emergence of zoonotic diseases such as Highly Pathogenic Avian Influenza (HPAI) and Severe Acute Respiratory Syndrome (SARS) have contributed to dominant Global Health narratives around health securitisation and pandemic preparedness, calling for greater co-operation between the health, veterinary and environmental sectors in the ever-evolving One Health movement. A decade later, One Health advocates face increasing pressure to translate the approach from theory into action.A qualitative case study methodology was used to examine the emerging relationships between international One Health dialogue and its practical implementation in the African health policy context. A series of Key Informant Interviews (n = 32) with policy makers, government officials and academics in Nigeria, Tanzania and Uganda are presented as three separate case studies. Each case examines a significant aspect of One Health operationalisation, framed around the control of both emerging and Neglected Zoonotic Diseases including HPAI, Human African Trypanosomiasis and rabies. The research found that while there is general enthusiasm and a strong affirmative argument for adoption of One Health approaches in Africa, identifying alternative contexts away from a narrow focus on pandemics will help broaden its appeal, particularly for national or regionally significant endemic and neglected diseases not usually addressed under a "global" remit.There is no 'one size fits all' approach to achieving the intersectoral collaboration, significant resource mobilisation and political co-operation required to realise a One Health approach. Individual country requirements cannot be underestimated, dismissed or prescribed in a top down manner. This article contributes to the growing discussion regarding not whether One Health should be operationalised, but how this may be achieved.